81.7k views
2 votes
Use the equation, (1/27)^x = 3^-4x+6, to complete the following problems

(a) Rewrite the equation using the same base.
(b) Solve for x. Write your answer as a fraction in simplest form.

User AHJeebon
by
4.7k points

1 Answer

11 votes

Answer:


\sf 3^(-3x)=3^((-4x+6))


\sf x=6

Explanation:


\sf Given \ equation: \left((1)/(27)\right)^x=3^((-4x+6))


\sf As \ (1)/(27)=(1)/(3^3) \ and \ (1)/(a^b)=a^(-b) \ then \ (1)/(27)=3^(-3)

Therefore, we can rewrite the given equation with base 3:


\implies \sf (3^(-3))^x=3^((-4x+6))

Apply the exponent rule
\sf (a^b)^c=a^(bc) :


\implies \sf 3^(-3x)=3^((-4x+6))


\sf If \ a^(f(x))=a^(g(x)) \ then \ f(x)=g(x)


\implies -3x=-4x+6

Add 4x to both sides to solve for x:


\implies \sf x=6

User Barbaris
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.